Metabolic, cellular and defense responses to single and co-exposure to carbamazepine and methylmercury in Dreissena polymorpha. (1st May 2022) - Baratange, Clément; Paris-Palacios, Séverine; Bonnard, Isabelle; Delahaut, Laurence; Grandjean, Dominique; Wortham, Laurence; Sayen, Stéphanie; Gallorini, Andrea; Michel, Jean; Renault, David; Breider, Florian; Loizeau, Jean-Luc; et al.
Abstract: Carbamazepine (CBZ) and Hg are widespread and persistent micropollutants in aquatic environments. Both pollutants are known to trigger similar toxicity mechanisms, e.g. reactive oxygen species (ROS) production. Here, their effects were assessed in the zebra mussel Dreissena polymorpha, frequently used as a freshwater model in ecotoxicology and biomonitoring. Single and co-exposures to CBZ (3.9 μg L −1 ) and MeHg (280 ng L −1 ) were performed for 1 and 7 days. Metabolomics analyses evidenced that the co-exposure was the most disturbing after 7 days, reducing the amount of 25 metabolites involved in protein synthesis, energy metabolism, antioxidant response and osmoregulation, and significantly altering cells and organelles' structure supporting a reduction of functions of gills and digestive glands. CBZ alone after 7 days decreased the amount of α-aminobutyric acid and had a moderate effect on the structure of mitochondria in digestive glands. MeHg alone had no effect on mussels' metabolome, but caused a significant alteration of cells and organelles' structure in gills and digestive glands. Single exposures and the co-exposure increased antioxidant responses vs control in gills and digestive glands, without resulting in lipid peroxidation, suggesting an increased ROS production caused by both pollutants. Data globally supported that a higher number of hyperactive cells compensated cellular alterations in the digestive gland of mussels exposed to CBZ or MeHg alone, while CBZ + MeHg co-exposure overwhelmed this compensation after 7 days. Those effects were unpredictable based on cellular responses to CBZ and MeHg alone, highlighting the need to consider molecular toxicity pathways for a better anticipation of effects of pollutants in biota in complex environmental conditions. Graphical abstract: Image 1 Highlights: Single and co-exposures caused ROS production and cellular damages. In single exposures, hyperactive cells compensated the cellular damage. Co-exposure overwhelmed this compensation modifying the metabolome.